Taxonomic relationship among four European Physokermes species (Hemiptera: Coccomorpha) based on nuclear and mitochondrial DNA - Marques, Joana F.; Winde, Inis; Jönsson, Anna Maria; Anderbrant, Olle (Frontiers in Forests and Global Change, 2023)
Scale insects (Hemiptera: Coccomorpha) feed on a wide variety of agricultural crops and forest and ornamental trees worldwide. These pest insects injure plants by causing sap loss but also by reducing the plant photosynthetic activity. This is because the honeydew they produce acts as substrate for mold, which covers leaf surfaces. In the last decades, several outbreaks of Physokermes spp. (soft scale insects) have occurred throughout Europe and partly been attributed to unusual weather conditions or climate change, as some species seem to be expanding their distribution range. However, the small size of these insects and their large intra-specific morphological variation have hindered the identification of the species responsible for outbreaks. In the present study, both mitochondrial and nuclear DNA markers were used to reconstruct the phylogenetic relationships of four Physokermes species sampled throughout Europe in 2013-2015. The results allowed to clearly distinguish P. hellenicus and P. inopinatus from each other and from the two closely related P. piceae and P. hemicryphys, confirming the value of using both nuclear and mitochondrial DNA markers for identifying scale insects. Further investigations are required to determine the taxonomic status of P. piceae and P. hemicryphys, which seem to comprise a species complex.